Alexander Fleming (1881-1955) : da descoberta da penicilina (1982) ao prémio Nobel (1945) - Pereira, Ana Leonor; Pita, João Rui (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Alexander Fleming’s discovery of penicillin in 1928 is one of the most distinguished scientific discoveries in the history of science, medicine and pharmaceutics of the 20th century. The authors point out the importance of this discovery and the transformation of penicillin into medication. Then, they present the results of their research regarding the reception of penicillin in Portugal during the second half of the 1940s.